Family Environment and Its Effect on Self Esteem and Adjustment Behaviour among School Children: A Cross Sectional Study from Hubli Taluka, Dharwad, Karnataka - Rana Sarvar; Anjana Joshi; Dattatraya D Bant (Medsci Publications, 2022)
Background: Family environment plays a significant role in socio-emotional and educational adjustment in adolescents. In the present scenario, parents are in hurry to improve their standard of living and they have no time to engage in child-bearing activities. Low self-esteem is creating mental and psycho-social problems such as poor academic achievement, inadequate adjustments among the siblings and peers, impaired social functioning, suicide, and substance abuse among adolescents. Methodology: A School-based cross-sectional study was conducted among adolescents of Hubli taluka. Information was collected by a self-administered questionnaire with components for Systematic assessment of family environment (SAFE), Self-esteem scale, and Adjustment inventory for school students (AISS). Results: Among 600 adolescents, 85.6% of adolescents had Normal self-esteem, 95%of families were competent, however only 1-7% of the students had an excellent adjustment. Emotional and social adjustment was better compared to Educational adjustment. Adjustment behavior and family environment had a positive association. There was a significant difference in the adjustment scores among low self-esteem and normal self-esteem (p<0.001) and also among discordant and competent families. Conclusion: The adjustment behavior depends on a better family environment and normal self-esteem. The Family environment has a positive effect on self-esteem as well as adjustment behavior. School mental health services should be initiated.